2007
DOI: 10.1002/adma.200602447
|View full text |Cite
|
Sign up to set email alerts
|

Organic–Inorganic Hybrid Hollow Spheres Prepared from TiO2‐Stabilized Pickering Emulsion Polymerization

Abstract: Organic–inorganic hybrid hollow spheres are prepared by using a TiO2‐stabilized Pickering emulsion polymerization method (see figure). By self‐organization of TiO2 nanoparticles at the interface of oil (monomer and solvent) and water, colloidosomes are formed and used as polymerization vessels to obtain the hybrid hollow spheres. The diameter and mechanical stability can be tailored by varying the relative amount of oil phase and the relative amount of divinylbenzene (DVB) in the monomer, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
264
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(278 citation statements)
references
References 23 publications
8
264
0
1
Order By: Relevance
“…A shift of interest in the area of Pickering suspension polymerization towards the morphologies of the polymerized emulsion droplets was reported by Bon and coworkers [93][94][95][96]. They demonstrated that microgels of poly(methyl methacrylateco-divinylbenzene) could be used to stabilize emulsion droplets composed of various monomers, i.e., styrene, DVB, and n-butylacrylate [93].…”
Section: Polymerization Of Emulsion Droplets Armored With Inorganic Nmentioning
confidence: 99%
See 1 more Smart Citation
“…A shift of interest in the area of Pickering suspension polymerization towards the morphologies of the polymerized emulsion droplets was reported by Bon and coworkers [93][94][95][96]. They demonstrated that microgels of poly(methyl methacrylateco-divinylbenzene) could be used to stabilize emulsion droplets composed of various monomers, i.e., styrene, DVB, and n-butylacrylate [93].…”
Section: Polymerization Of Emulsion Droplets Armored With Inorganic Nmentioning
confidence: 99%
“…150 nm in diameter) armored microspheres and capsules made via Pickering suspension polymerization of styrene and DVB. For the capsules hexadecane was used as non-solvent for the polymer [95]. Upon polymerization, the polymer phase-separated at the interface of the droplet.…”
Section: Polymerization Of Emulsion Droplets Armored With Inorganic Nmentioning
confidence: 99%
“…So-called Pickering emulsion polymerization has been exploited to produce a range of microcapsules. [43][44][45] Poly(methyl methacrylate) particles have been adsorbed around monomer droplets containing styrene and divinylbenzene and subsequently used as mini-reaction vessels for copolymerization from within the droplet phase. 43 This led to the formation of colloidosomes of 5 to 30 µm diameter reinforced by solid cross-linked polystyrene cores.…”
Section: Polymerization After Pickering Emulsion Formationmentioning
confidence: 99%
“…As a solution, one can force polymer and inorganic phases to interact at a molecular level and upscale the physical properties of the ultimate composite material (7,8). A standard technique for hybrid organic-inorganic material formation uses either hollow particles (9)(10)(11) or capsules (12,13). Due to their ability to encapsulate versatile functional cargos; these methods gained wide applications in catalysis (14), drug-delivery systems (15,16), biology (17), coatings (18,19), and so on.…”
Section: Introductionmentioning
confidence: 99%